Talking television an introduction to the study of television - Burton, Graeme (Arnold Co-published in the United States of America by Oxford University Press, 2000)
This textbook introduces students to three main approaches to television studies: culturalist, postmodernist and gender perspectives. It explores key concepts such as ideology, institution and audience, and TV genres such as docusoaps.